Armenian Atrocities Against Azerbaijanis in the Ancient Oghuz-Turkic Homeland of Zangazur at the Beginning of the 20th Century (Based on Archival Materials) - Abdulla Mustafayev (Jurnal Mengkaji Indonesia, 2025)
Abstract: It was mentioned in the article that the Armenians, who were resettled in the lands of ancient Azerbaijan under the patronage of Tsarist Russia at the beginning of the 19th century, completed their military, political, economic, organizational and ideological preparations to seize these lands and started provocative actions from the beginning of the 20th century. They used various means to create fear among the population, and took advantage of the indifference of the tsarist authorities to become even more perverted. Finally, trying to take advantage of the conditions created by the first bourgeois-democratic revolution in Russia, they began to implement the first stage of the genocide and deportation policy that they would carry out against Azerbaijanis at various times throughout the 20th century. Purpose: This article investigates the systematic violence and atrocities committed by Armenian armed groups, particularly the Dashnaksutyun party, against Azerbaijanis in the Zangezur district at the beginning of the 20th century. The aim is to bring international attention to this overlooked historical episode and examine the policies of ethnic cleansing and demographic manipulation carried out against the Azerbaijani population. Design/Methodology/Approach: This study adopts a qualitative historical research method by analyzing archival materials, periodicals, and works of both Azerbaijani and Armenian authors. It employs document analysis to explore multiple narratives and reconstruct the events that transpired in the South Caucasus region during 1905–1907. Findings: The research reveals that Armenian militias, aided by Russian imperial authorities, launched coordinated attacks on Azerbaijani settlements, resulting in mass killings, forced displacement, and the destruction of over 40 villages. Despite local resistance and organized counterattacks by Azerbaijani defense groups, many villages such as Qatar, Okchu, and Shabadek fell under siege and witnessed horrific massacres. The violence altered the ethno-demographic balance in favor of Armenians, with a significant decline in Azerbaijani presence in the Iravan governorate. Originality/value: The article contributes original insights by presenting underrepresented Azerbaijani perspectives, substantiated through rarely accessed archival records. It challenges dominant narratives that overlook these atrocities and exposes the long-standing effects of Armenian expansionist nationalism and Russian imperial complicity. The study underscores the need for historical justice and a re-evaluation of early 20th-century Caucasus history to foster reconciliation and understanding.